Real-time Systems - Kuodi Jian (IntechOpen, 2016)
This book is dedicated to Real-time Systems of broad applications, such as autonavigation (Kalman Filtering), real-time reconfiguration of distributed networks, real-time bilateral teleoperation control system over imperfect networks, and uniform interfaces for resource-sharing components in hierarchically scheduled real-time systems. In addition to that, wireless technology and its usage in implementing intelligent systems open a wide spectrum of real-time systems and offer great potential for improving people’s life: for example, wireless sensor networks used in subways, reduced energy consumption in public buildings, improved security through public surveillance, and high efficiency through industrial automation. Furthermore, electric utilities and multi-core CPU architecture, the driving force of modern life, are part of subjects benefited from the topics covered in this book.